Theatre pedagogy in the era of climate crisis - Fancy, David; Alexandrowicz, Conrad (Research and teaching in environmental studies., 2021)
"This volume explores whether theatre pedagogy can and should be transformed in response to the global climate crisis. Conrad Alexandrowicz and David Fancy present an innovative re-imagining of the ways in which the art of theatre, and the pedagogical apparatus that feeds and supports it, might contribute to global efforts in climate protest and action. Comprised of contributions from a broad range of scholars and practitioners, the volume explores whether an adherence to aesthetic values can be preserved when art is instrumentalized as protest, and considers theatre as a tool to be employed by the School Strike for Climate movement. Considering perspectives from areas including performance, directing, production, design, theory and history, this book will prompt vital discussions which could transform curricular design and implementation in the light of the climate crisis. Theatre Pedagogy in the Era of Climate Crisis will be of great interest to students, scholars and practitioners of climate change and theatre and performance studies"-- Provided by publisher.